Technologies of formation of teachers' readiness for innovative activity (Journal of Educational Sciences, 2021)
The new requirements put the professional training of teachers with modern high professional qual- ifications in the first place. In the system of pedagogical Sciences, innovative activity is defined as purposeful pedagogical activity based on understanding one’s own pedagogical experience through changing and developing the educational process in order to analyze and study, achieve high results, gain new knowledge, and introduce a qualitatively different pedagogical experience. Preparation for teaching activities is a crucial aspect of the formation and self-development of a teacher throughout his life. Moreover, the formation of innovative teacher training is an increase in the contribution of a new paradigm to the development of society, implementing world competitive education; acceleration of the implementation of innovative reforms in educational institutions; widespread use of innovative changes in the education system, new information and communication technologies in the educational process.The article considers the scientific directions on the formation of the teacher’s readiness for inno- vation, and also suggests ways to improve and form the readiness of the lecturers for innovation. The authors suggest the nature of teachers ‘ readiness for innovation, focusing on the scientific conclusions of well-known teachers. They also present the results of a small research work.Key words: innovation, activity, psychological and pedagogical training, innovative activity.